Stem/Progenitor Cell Niches Involved in Hepatic and Biliary Regeneration - Guido Carpino; Anastasia Renzi; Antonio Franchitto; Vincenzo Cardinale; Paolo Onori; Lola Reid; Domenico Alvaro; Eugenio Gaudio (Stem Cells International)
Niches containing stem/progenitor cells are present in different anatomical locations along the human biliary tree and within liver acini. The most primitive stem/progenitors, biliary tree stem/progenitor cells (BTSCs), reside within peribiliary glands located throughout large extrahepatic and intrahepatic bile ducts. BTSCs are multipotent and can differentiate towards hepatic and pancreatic cell fates. These niches’ matrix chemistry and other characteristics are undefined. Canals of Hering (bile ductules) are found periportally and contain hepatic stem/progenitor cells (HpSCs), participating in the renewal of small intrahepatic bile ducts and being precursors to hepatocytes and cholangiocytes. The niches also contain precursors to hepatic stellate cells and endothelia, macrophages, and have a matrix chemistry rich in hyaluronans, minimally sulfated proteoglycans, fetal collagens, and laminin. The microenvironment furnishes key signals driving HpSC activation and differentiation. Newly discovered third niches are pericentral within hepatic acini, contain Axin2+ unipotent hepatocytic progenitors linked on their lateral borders to endothelia forming the central vein, and contribute to normal turnover of mature hepatocytes. Their relationship to the other stem/progenitors is undefined. Stem/progenitor niches have important implications in regenerative medicine for the liver and biliary tree and in pathogenic processes leading to diseases of these tissues.